1.31 and 1.32 μm dual-wavelength Nd:LuLiF4 laser. (July 2016) - Li, Shixia; Li, Tao; Zhao, Shengzhi; Li, Guiqiu; Hang, Yin; Zhang, Peixiong
Abstract: We demonstrate the operation of Nd:LuLiF4 laser with efficient 1.31 and 1.32 μm dual-wavelength. Maximum continuous-wave output power of 1.63 W is obtained at an incident pump power of 9.97 W and 8% transmission of output coupler (OC), giving a slope efficiency of 17.9%. When monolayer graphene is employed as saturable absorber, stable passively Q-switched 1.31 and 1.32 μm dual-wavelength laser operation still remains. The maximum average output power of 1.33 W, the largest pulse energy of 17.3 μJ and the highest peak power of 111.6 W are achieved with the 8% OC. Meanwhile, the shortest pulse duration of 133 ns and the highest repetition rate of 91 kHz are rendered by the 3.8% OC cavity. Highlights: The 1.31 and 1.32 μm CW dual-wavelength Nd:LuLiF4 laser has been reported. Higher output power is obtained by higher transmission of output coupler. Employing graphene as SA, QS dual-wavelength Nd:LuLiF4 lasers were obtained. Shorter pulse duration was achieved by the lower transmission of output coupler.